Perceptions of Pre-service Teachers on Impact of Language Learning Strategies - Kadel, Purna Bahadur (Molung Educational Frontier, 2022)
This study attempts to identify pre-service teachers' perceptions on the impact of language learning strategies to achieve their academic performances and to findout the importance of language learning strategies to be self-regulated learners. This is a narrative inquiry research design in which an in-depth interview was used as a tool to collect data. Six pre-service teachers who have been studying in Master of Education English fourth semester were selected using a purposive, non-random sampling procedure. The findings of this study show that language learning strategies help second language learners be self-regulated learners; they help them learn quickly, fast, and effectively and help them encounter complicated tasks. Furthermore, language learning strategies help them to develop their self-assessment skills and enhance cooperation and collaborative learning.